Influence of the cassava harvest month on the sensory parameters of attiéké - Allou Christian Armel Gnamien; Amoikon Tiemele Laurent Simon; Adingra Kouassi Martial-Didier; Brou Koffi Siméon; Tano Kablan (Journal La Lifesci, 2021)
Cassava is an important staple food around the world, especially in Africa. It is cultivated throughout the Ivorian territory with predominance in the South. Due to the high demand, some producers opt for an early harvest, neglecting the impact of the harvest stage on the sensory parameters of cassava root derivatives. The objective of this work was to determine the stage of harvest allowing obtaining products of good sensory quality. The sensory characteristics of the attiéké were evaluated at different stages of harvest (11th, 12th, 13th and 14th months after planting the cuttings) of the cassava roots of the Yacé variety which were used for its production. The attiéké obtained in the twelfth month of harvest was generally much appreciated because it was less acidic, less fibrous and more homogeneous and had a better smell. Thus, cassava harvested in the twelfth month of cultivation makes it possible to obtain attiéké with the best sensory characteristics. Therefore, this stage of maturity of cassava roots is recommended for attiéké producers.